Boron nitride and hyperbranched polyamide assembled recyclable polyisoprene vitrimer with robust mechanical properties, high thermal conductivity and remoldability. (3rd November 2020) - Huang, Lingyun; Yang, Yinxin; Wu, Ruiyao; Fan, Weifeng; Dai, Quanquan; He, Jianyun; Bai, Chenxi
Abstract: Rubber has huge potential applications for thermal management due to its outstanding softness and elasticity, however, its low thermal conductivity limits its applications, and the vulcanized rubber also has the problem of being unrecoverable. Therefore, the development of recyclable rubber-based material with good mechanical properties, high thermal conductivity remains a challenge. Herein, the dynamic β-hydroxyl ester bonds were introduced into the composites of the epoxidized boron nitride (EBN) and the epoxidized polyisoprene (EPI) matrix via carboxyl-terminated hyperbranched polyamide (HBPA), forming dynamic covalently cross-linking rubber-based vitrimers. The covalent-bonds-mediated interface reduces the phonon scattering and enables the material to have a relatively high thermal conductivity of 0.51 W/mK under a loading of 50 phr (parts per one hundred parts of rubber) of EBN. In addition, the introduction of exchangeable bonds brings the materials the capability to change the network topology at high temperatures, exhibiting excellent recyclability and remoldability. Graphical abstract: Image 1 Highlights: Rubber-based vitrimer with mechanical robustness, recyclability and remoldability. High efficiency for thermal conductivity enhancement. Facile strategy for constructing dynamic cross-linking network. Smart application of hyperbranched polymer for uniform dispersion of BN in rubber.